2012
DOI: 10.1021/cm301685x
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Nanoparticles and Proton Conductivity: Improving Proton Conductivity of BaCe0.9Y0.1O3−δ Using a Catalytic Approach

Abstract: In this work, we have used nickel nanoparticles to improve proton conductivity of the electrolyte BaCe0.9Y0.1O3−δ (BCY). Ni nanoparticles were dissolved into the compounds as their oxidized form (BaCe0.9–x Y0.1Ni x O3−δ) and precipitated upon heating under a reducing atmosphere. Below 700 °C, proton conductivity is enhanced under a reducing atmosphere. An increase of 1 order of magnitude, with respect to BCY, was observed for BaCe0.7Y0.1Ni0.2O3−δ (1.7 × 10–2 S/cm at 500 °C). This phenomenon is more pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…2E), group 3 dopants, produced microstroctures that were similar, or worse, than the BCZY63 control sample, despite having similar sintering conditions (1600 o C for 12 h). PdO is thought to create a small increase in point defect concentrations, a hypothesis which we along with others have previously proposed [14][15][16][17]. Thus we expect its grain size and density to be comparable or slightly better than the control.…”
Section: Microstructurementioning
confidence: 52%
“…2E), group 3 dopants, produced microstroctures that were similar, or worse, than the BCZY63 control sample, despite having similar sintering conditions (1600 o C for 12 h). PdO is thought to create a small increase in point defect concentrations, a hypothesis which we along with others have previously proposed [14][15][16][17]. Thus we expect its grain size and density to be comparable or slightly better than the control.…”
Section: Microstructurementioning
confidence: 52%
“…In the literature, the exsolution of metallic nanoparticles such as Ni dissolved as an oxide by cationic substitution into the compound and precipitated under reductive atmosphere after heating has been reported in nonstoichiometric perovskites, 28 and it was shown to increase the electrocatalytic properties. 29,30 In the same way, the presence of metallic molybdenum could enhance the electronic and catalytic properties of the materials. However, the decomposition into metallic molybdenum suggests that amorphous phase La 2 Mo 2 O 7−y is not thermodynamically stable under reductive atmosphere, as already mentioned by Vega-Castillo et al 10 Indeed, the reduction kinetics under diluted H 2 is very slow (Figures 2 and 4) but does not show any stabilization of the oxygen content of the amorphous phase: according to the model, the kinetic constant of Reaction C is very weak, and a correlatively very long reduction time would lead to full decomposition into metallic Mo.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…This effect was ascribed to the formation of percolating space-charge layers with depleted charge carrier concentration around the metal particles. Caldes et al, on the other hand, reported an increase in the electrical conductivity of acceptor-doped BaCeO 3 containing Ni nanoparticles and attributed that to the enhanced catalytic splitting of H 2 resulting in enrichment of OH O • near the Ni particles. Moreover, Clark et al reported enhanced proton conductivity in Y- and Yb-co-doped BaZrO 3 containing Ni particles.…”
Section: Introductionmentioning
confidence: 99%